Peran Pemamoan Dalam Adat Perkawinan Suku Kluet di Gampong Ruak Kecamatan Kluet Utara Kabupaten Aceh Selatan - Masriati Masriati; Misri A. Muchsin; Muhammad Yunus Ahmad (Jurnal Adabiya, 2022)
This thesis will discuss about "The Role of Pemamoan in the Marriage Custom of the Kluet Tribe in Gampong Ruak, North Kluet District, South Aceh Regency". This study aims to explain about pemoan, the role of pemoan in the marriage customs of the Kluet tribe in Gampong Ruak and the community's response to the role of pemoan in the marriage customs of the Kluet tribe in Gampong Ruak. The method used in this research is using a descriptive qualitative approach. This research was conducted in Gampong Ruak, North Kluet District, South Aceh Regency, which became the object of research was the Gampong Ruak community who had been the guardian of the marriage customs of the Kluet tribe in Gampong Ruak. The data collection techniques used include observation, interviews and documentation, as well as using data analysis techniques as a complement. The data analysis technique is divided into three activity lines which include data reduction, data presentation and conclusion drawing. The results of this study indicate that pemoan is an uncle or brother from the mother's side, pemoan plays a role in taking care of all the needs of the bride and groom, and the Gampong Ruak community responds well and accepts the role of pemoan in the marriage customs of the Kluet tribe in Indonesia. Gampong Ruak, North Kluet District, South Aceh Regency